Aproximación a un plan de negocios para la fabricación y exportación de láminas de fibra de carbono (2020)
The following document is created in order to design an approach company dedicated to the manufacturing of carbon fiber and its exporting worldwide, this design proposes a high impact business model within the company and the consumers. In order to pursue the necessities of modern customers, the company needs specific ideals, dynamic activities with integrated, efficient, fast and fully digitized processes harmonized with environmental sustainability and corporate social responsibility.